보건행정자의 자격배경 및 지도력 유형에 따른 보건간호원의 만족도와 직무만족도에 대한 조사 연구 : 서울시내 보건소를 중심으로 - 오성희 (연세대학교 보건대학원, 1987)
[한글] 사회의 변천과 과학·기술의 발전으로 건강과 간호에 대한 사회적 요구가 달라졌다. 이러한 사회적 요구에 부응하기 위해 모든 인간의 건강요구를 효율적으로 충족시키는데 그 목적을 두고 있으며 건강관리사업의 일익을 담당하고 있는 지역사회 간호사업은 지역사회 및 주민의 건강요구를 효과적으로 충족시키는데 그 목적을 두고 있다. 우리나라의 경우 이는 보건소에 근무하는 보건간호원을 중심으로 수행되고 있다. 그러므로 지역사회 및 주민의 효과적으로 충족시키기 위해서는 보건간호원의 효율적인 관리가 우선 되어야 한다. 이를 위하여 본 연구자는 보건행정자의 자격배경에 따른 지도력과 보건간호원의 보건행정자에 대한 만족도와 직무만족도의 관계를 규명하여 보건간호원의 효율적인 관리를 위한 보건간호행정에 도움이 될 기초자료를 제공하고자 본 연구를 시도하였다. 연구대상은 서울시내 보건소에 근무하는 보건행정자(계장) 58명과 보건간호원 157명이었다. 자료수집 기간은 1986년 9월22일∼10월4일까지 14일간이었으며, 연구도구는 지도력 행동과 지도자에 대한 만족도와 직무만족도를 측정하는 표준화된 3개의 측정도구를 사용하였다. 수집된 자료는 SPSS를 이용하여 백분율, 평균, ANOVA, T-test, Pearson상관관계 분석 등의 통계방법으로 처리하였다. 연구의 결과를 요약하면 다음과 같다. 1. "간호원 자격배경을 가진-보건행정자 하에 있는 보건간호원들이 간호원 자격배경을 갖지않은-보건행정자 하에 있는 보건간호원들보다 그들의 보건행정자에 대한 만족도 높을 것이다"는 제1가설은 기각되었다(t=-.56, p>0.01). 2. "보건간호원은 보건행정자의 지도력 유형중 인간관계와 업무중심형(I), 인간관계 중심형(Ⅱ), 업무중심형(Ⅲ), 방임형(Ⅳ)의 순으로 보건행정자에 대한 만족도가 나타날 것이다"는 제2가설은 채택되었다.(F=9.58, p<0.001). 3. "보건간호원의 보건행정자에 대한 만족도는 직무만족도와 긍정적인 상관관계가 있을 것이다"는 제3가설이 채택되었다(r=.2899, p<0.001). 4. 보건행정자의 일반적인 특성에 따른 지도력유형과 보건행정자에 대한 만족도의 분석에서는 보건행정자의 학력, 경력, 보건간호원과 함께 일한 기간은 지도력 유형과 유의한 차이를 보이지 않았고, 나이만 통계학적으로 유의한 차이를 보였으나 지도력 유형을 결정 짓는 요인은 아니었다. 또 보건행정자의 나이, 학력, 경력, 보건간호원과 함께 일한 기간은 보건간호원의 보건행정자에 대한 만족도에 영향을 주지 않았다. 5. 보건간호원 및 보건행정자가 각각 측정한 보건행정자의 지도력 행동점수(인간관계와 업무수행)에 관한 비교분석에서는 업무수행에 관한 행동점수는 유의한 차이를 보이지 않았으나 인간관계에 관한 행동점수는 통계학적으로 유의한 차이를 보였다. 결론적으로 보건행정자의 간호원 자격배경 유무에 관계없이 업무수행과 인간관계에 모두 역점을 두는 지도력유형하에 있는 보건행정자에 대해 가장 높은 만족도를 나타냈다. 또 보건행정자에 대한 만족도가 높을수록 직무만족도가 높았다. 그러므로 보건간호원의 직무만족도를 높여 지역사회 간호업무의 효율성 증진과 전문직 발전을 꾀하기 위하여 보건행정자는 보건간호원과의 관계에서 인간관계와 업무수행에 모두 역점을 두는 지도력 행태를 취하는 것이 바람직하다고 사려된다. [영문] As society has changed and science and technics have developed, the demand for improved health care and nursing care has increased. To keep up with this kind of social need, modern nursing care is seeking; to efficiently satisfy the health care needs of human beings. The purpose Public health nursing, one of the health services in the community is purpose to satisfy nursing care need of community people. It is performed mainly by public health nurses in health clinics. Therefore efficient nursing performance depends greatly on efficient in management. The purpose of this study was to obtain information to obtain information to help in management and to increase the job satisfaction of the public health nurse by determining the leadership style and background of the public health administrator which is satisfying to the public health nurses and determining the relationship between public health nurses' job satis faction and their satisfaction with the public health administrator. The subjects for this study were 58 public health managers and 157 public health nurses in the health clinics located in Seoul. The survey for the study was done from Sept. 22 to Oct. 4th, 1986 using instrument with was three standardized measuring sealers for measurement of leading behavior, satisfaction with the leader sod job satisfaction. The analysis of data was done using percentage, mean and Pearson corrlation, ANOVA, T test. The results of this study are as follows; 1. Test of Hypothesis (a) Hypothesis I is that Public health nurses working under the Public health administrator has a nursing background will be more highly satisfied wish the public health administrator than those working under administrators with non-nursing background was rejected(t=-.56, p>0.01). (b) Hypothesis Ⅱ that the Public health nurse's satisfaction with the public health administrator will be in the following order: human relation & task-oriented style, human relation-oriented style, task-oriented style, non-curing style was accepted(F=7.58, p<0.001). (c) Hypothesis Ⅲ that Public health nurses' satisfaction with the public health administrator will be positively related to their job satisfaction was accepted(r=.2899, p<0.001). 2. Analysis of the relationship between the public health administrator's general characteristics and the Leadership style of the public health administrator and the public health nurse's satisfaction with the public health administrator. The leadership style of the public health administrators was not related to their education, years of experience and the number of years that the public health nurses had worked under the public health administrator. The leadership style of the public health administrator and their age were statistical significant, but there was no consistant leadership style pattern. The age, educational and yearn of experience of the public health administrator and the number of years that the public health nurses worked under the public health administrators did not show any relationship to the nursers satisfaction with the public health administrators. 3. Analysis of the public health administrator and nurse measures seperately leadership behavior between human relation and task-oriented style: The leadership behavior of human relation style is satistical significant, but task-oriented style is not-significant.
보건학과/석사